Land as an Environmental Resource - Hart, Kaley; Allen, K.; Lindner, Marcus; Keenleyside, C.; Burgess, Paul J.; Eggers, J.; Buckwell, A. (Cranfield University, 2013)
Report Prepared for DG Environment, Contract No ENV.B.1/ETU/2011/0029, Institute for European Environmental Policy, London. Land is a multifunctional resource and the amount available to be used for different purposes is relatively fixed. This study focuses on the rural land resource and its essential role in delivering all ecosystem services, including food, timber, biomass for energy, clean water, healthy soils, carbon sequestration, cultural landscapes and recreational space, underpinned by biodiversity. Some of these ecosystem services, such as crops, livestock and timber do not have to be produced within the EU to be enjoyed by EU consumers as they can be traded. Others, notably environmental services such as clean water are location specific and have to be produced within the EU, for European citizens to benefit from them. Consequently, while the main concern of this study is land use in the EU, it must be recognised that a larger area of the world, including land in many other countries, is deployed to meet the needs of European citizens. This ‘footprint' overseas needs to take account of exports too, but includes land growing food, livestock feed, fibre, wood, bioenergy feedstocks and other commodities, as well as less quantifiable, but important, services provided by forests and other ecosystems. With large scale trade in commodities in and out of the EU, there is a dynamic interplay between land uses, which need to be taken into account. EU land use cannot be considered in isolation. To meet the multiple demands being placed upon rural land in a way that is sustainable and promotes the efficient use of natural resources, policy decisions have to be made about the appropriate use of the available resource in any given location and situation. These can guide, influence and, in some cases, regulate the decision of land owners and managers. The need for a coherent approach to land use and its integration into key policy areas is therefore paramount. The purpose of the study is to consider the range of demands facing different types of rural land use and related ecosystem services in the EU to 2050 and, in light of these, to examine the various ways in which these demands could be met.